First-line immune checkpoint inhibitors combined with chemotherapy in advanced large-cell neuroendocrine carcinoma of the lung: a real-world retrospective study - Ji, Beibei; Luan, Wei; Sha, Rula; Li, Wenxin (Frontiers in Oncology, 2025)
BackgroundLarge-cell neuroendocrine carcinoma of the lung (LCNEC) shares clinicopathological features with both small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). Owing to its neuroendocrine characteristics, the treatment of LCNEC often follows paradigms established for SCLC. Immune checkpoint inhibitors (ICIs) have become the standard first-line therapy for extensive-stage SCLC (ES-SCLC), but evidence supporting the use of ICIs in advanced LCNEC remains limited. This study aimed to evaluate the efficacy and prognosis of first-line ICIs in patients with advanced LCNEC.MethodsWe retrospectively analyzed 31 patients with stage IV LCNEC treated at Inner Mongolia People’s Hospital from January 2019 to December 2024. Of these, 14 patients received ICIs plus platinum-based chemotherapy (the ICIs + Chemo group), and the other 17 patients received chemotherapy alone (the Chemo group). Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events(AEs) were compared between the two groups.ResultsAfter a median follow-up of 24 months, the ICIs + Chemo group demonstrated significantly longer median PFS (10.5 months [95% CI, 7.6-12.4] vs. 6.0 months [95% CI, 4.3-7.7]; p=0.035) and median OS (15.0 months [95% CI, 11.4-18.6] vs. 11.0 months [95% CI, 9.3-12.6]; p=0.036) compared to the Chemo group. Multivariate Cox regression showed that the ICIs + Chemo group reduced the risk of progression by 49% (HR = 0.51; 95% CI, 0.28-0.92; p=0.026) and death by 45% (HR = 0.55; 95% CI, 0.30-1.01; p=0.054). The ORR and DCR were 50.0% and 85.7% in the ICIs + Chemo group, versus 29.4% and 76.5% in the Chemo group, respectively. Immune-related adverse events (irAEs) in the ICIs + Chemo group were grade 1–2, with no grade 3 or higher adverse events observed.ConclusionThis study was based on real-world data from northern China. Preliminary findings suggest that ICIs combined with chemotherapy may be a promising treatment option for patients with advanced LCNEC, with potential survival benefits. However, as a single-center retrospective study with a limited sample size, further multi-center and large-sample prospective clinical trials are warranted to validate these results.